AB0877 Sleep quality in patients with ankylosing spondylitis. (23rd January 2014) - Aydin, E.; Bayraktar, K.; Turan, Y.; Kurt Omurlu, I.; Tastaban, E.; Sendur, O.F.
Abstract : Background: The main clinical phenomena in ankylosing spondylitis (AS) are pain and body limitation which effect daily activities and quality of life. Because of the postural alterations, inflammatory night pain and stiffness, sleep disturbances are also likely in patients with ankylosing spondilitis. There is a number of studies that demonstrate poor sleep quality in these patients. Objectives: This study aimed to determine differences in sleep quality between patients with AS and healthy controls and to assess relationship between disease activity and sleep quality in AS patients. Methods: Forty patients with AS (29 men, 11 women; age, 44±9 yrs) who fulfilled the modified New York criteria and forty comparable controls (29 men, 11 women; age, 43±9 yrs) completed the Pittsburgh sleep quality index (PSQI) to assess sleep quality. BASDAI was collected for assessing disease activity. Results: Significant differences in sleep disturbances (P=0.044), daytime dysfunction (p=0.027) and total PSQI score (P=0.017) but not for the sleep quality, sleep latency, sleep duration, habitual sleep efficiency and sleep medication use were found; between patients with AS and healthy controls. Significant positive correlations between BASDAI scores with sleep quality (P=0.008), sleep latency (P=0.006), sleep duration (P=0.015), habitual sleep efficiency (P=0.003), sleep disturbances (P=0.002), day time dysfunction (P<0.001) and total PSQI score (P<0.001) were found in patients with AS. In addition, BASDAI scores that suggest active disease (≥4) were significantly correlated with sleep quality (P=0.02), sleep latency (P=0.003), habitual sleep efficiency (P=0.014), sleep disturbances (P=0.019), day time dysfunction (P=0.027) and total PSQI score (p<0.001). Conclusions: In the current study, we found that sleep disturbances were significantly higher in patients with AS and disease activity was associated with sleep quality. References: Günaydin R, Göksel Karatepe A, Cesmeli N, Kaya T. Fatigue in patients with ankylosing spondylitis: relationships with disease-specific variables, depression, and sleep disturbance. Clin Rheumatol. 2009; 28(9):1045-51. Hultgren S, Broman JE, Gudbjörnsson B, Hetta J, Lindqvist U. Sleep disturbances in outpatients with ankylosing spondylitisa questionnaire study with gender implications. Scand J Rheumatol. 2000;29(6):365-9. Disclosure of Interest: None Declared